2013
DOI: 10.1111/jocs.12129
|View full text |Cite
|
Sign up to set email alerts
|

Alkaptonuria-Associated Aortic Stenosis

Abstract: Alkaptonuria is an autosomal recessive disorder of tyrosine metabolism, which results in accumulation of unmetabolized homogentisic acid and its oxidized product in various tissues, including the heart. Cardiovascular involvement is a rare but serious complication of the disease. We present two patients who have undergone successful aortic valve replacement for alkaptonuria-associated aortic stenosis along with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Results were very reproducible and revealed that pigmented areas were composed by C, O, N, S, Na, and variable amount of Ca. Sulphur is an element never reported before in cardiac valve tissue, and its constant presence in the pigment is probably due to the ability of HGA oxidized to BQA, to form adducts with protein thiols [6]. The white concretions (Figure 2(a)B) contained P and Ca that indicated the presence of hydroxyapatite.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Results were very reproducible and revealed that pigmented areas were composed by C, O, N, S, Na, and variable amount of Ca. Sulphur is an element never reported before in cardiac valve tissue, and its constant presence in the pigment is probably due to the ability of HGA oxidized to BQA, to form adducts with protein thiols [6]. The white concretions (Figure 2(a)B) contained P and Ca that indicated the presence of hydroxyapatite.…”
Section: Resultsmentioning
confidence: 91%
“…Mechanical stress, one of the typical functional features of heart valve, may be a linker between amyloid and ochronotic pigment copresence, since it has been reported to be responsible for both amyloid deposition [20, 24, 25] and ochronotic pigment deposition in AKU [6, 9]. Mechanical stress in heart valves has been positively related to oxidation of lipoproteins inducing calcification in pathologies [20, 25, 28, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The ochronotic chondrocyte pigmentation of a mouse model was also shown to follow an age-related pattern with the first signs of pigmentation restricted to the pericellular matrix surrounding individual chondrocytes, followed by eventual progression to the intracellular compartment (Preston et al 2014). The cartilaginous tissues and bone seem to be particularly susceptible resulting in widespread arthritis and joint destruction (Keller et al 2005) as well as deterioration of cardiac valves (Lok et al 2013). In fact a lack of HGD activity in human cardiac tissue was suggested as the cause of localised production of ochronotic pigment in AKU heart (Lok et al 2013).…”
Section: Pigmentation In Aku: the Nature Of The Pigmentmentioning
confidence: 99%
“…The cartilaginous tissues and bone seem to be particularly susceptible resulting in widespread arthritis and joint destruction (Keller et al 2005) as well as deterioration of cardiac valves (Lok et al 2013). In fact a lack of HGD activity in human cardiac tissue was suggested as the cause of localised production of ochronotic pigment in AKU heart (Lok et al 2013). It could be that other tissues affected by the disease with an enzyme defect have similar increased HGA and pigment production contributing to the induction of ochronotic arthropathy (Laschi et al 2012).…”
Section: Pigmentation In Aku: the Nature Of The Pigmentmentioning
confidence: 99%
“…An increased prevalence of aortic valve disease, and in particular aortic stenosis, is seen in patients with alkaptonuria compared to the general population [6]. In the Cardiovascular Health Study, which looked at 5621 patients aged 65 or older, 1.8% were found to have aortic stenosis [7].…”
Section: Discussionmentioning
confidence: 99%